The Totemic Features in the Islamic Sufi Societies (Journal of Namibian Studies : History Politics Culture, 2023)
This study explores the Totemic manifestations in the Islamic Sufi societies. Those manifestations involve a set of belief ideas that is found independently in religions, or a type of social organization of a number of human groups. On the other hand, Sufism is a religious-social phenomenon known of being characterized by the nature of the place in which it is originated or reach. Thus, one can investigate the totemic manifestations in the Sufi societies whether at the religious or social structural level. The approach: the researcher adopted the inductive approach through reviewing the foreign and Arab books and studies about Sufism and Totemism that are related to them in terms of concepts, and practices on the religious and social levels. In addition, the study relies on the comparative approach for comparing Totemism with Sufism so as to identify similarities. Finally, the researcher adopted the analytical approach to analyse and clarify those concepts, practices and similarities of both which leads to identify the totemic features in the Islamic Sufis societies. This research has reached a set of conclusions; the most important of which are: there are totemic characteristics – in varying degrees- in the Islamic Sufis societies. On the religious level; Totemism manifests in the aspects related to the holiness of totem and everything related to it, in addition to the protection of all individuals that fall under its logo, which resemble in its appearance and content sheikh al Method or the Walli in some Sufi orders, and the common manifestations in ritualistic practices represented in musical dancing worship practices that leads to ecstasy and Karamat (blessings). On the social level, Totemism characteristics manifest in Sufi groups. They are represented in the hierarchical societal organizational structure of Sufism, that makes the sheikh or Alwali (the totem) serve as the core element and the societal symbol of the Sufi method.